Endoscopic Ultrasound-Guided Hepatogastrostomy (EUS-HGS) as a Rescue Biliary Drainage Strategy: Experience in a Tertiary Care Hospital in Costa Rica. - Evans Rodríguez, Enrique (2025)
Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) is the standard treatment for biliary drainage, but it may fail in patients with advanced malignant obstruction. In such cases, endoscopic ultrasound-guided hepatogastrostomy (EUS-HGS) has emerged as an effective therapeutic alternative. This retrospective study describes the experience of Hospital San Juan de Dios, Costa Rica, with EUS-HGS as a rescue drainage strategy after failed ERCP. Objective: To describe the institutional experience with EUS-HGS as a biliary drainage technique in patients with unresectable malignant obstruction and failed ERCP, evaluating its technical feasibility, clinical efficacy, and safety in a high-complexity public center. Materials and Methods: Twenty consecutive patients treated with EUSHGS between April 2023 and March 2024 were included. Clinical success was defined as a ≥50% reduction in total bilirubin at 30 days. Adverse events, procedure time, and technical success were evaluated. Results: Technical success was achieved in 100% of cases (20/20). Nineteen patients (95%) reached clinical success. The mean procedure time was 18 minutes. No major complications or mortality were reported. Three patients (15%) presented mild adverse events (abdominal pain and minimal bleeding). Conclusion: EUS-HGS proved to be a safe, effective, and reproducible technique in patients with failed ERCP. The institutional experience supports its use in public centers with trained personnel, strengthening its role in the management of complex malignant biliary obstruction.